Penguatan Karakter Melalui Sosialisasi Pencegahan Tiga Dosa Besar Pendidikan di Desa Pasinan Kecamatan Lekok Kabupaten Pasuruan - Zhunnun Qothrunnada; Farida Nabilah; Rekha Widiawati; Wakid Evendi; M. Yusron Maulana El-Yunusi; Mila Hariani; Nelud Daraajatul Aliyah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Character strengthening activities through socialization on the prevention of the three educational sins were carried out for approximately 3 consecutive days at several schools in Pasinan Village, Lekok District, Pasuruan Regency, which were attended by elementary/MI students in grades V and VI. The purpose of this activity is so that participants can learn about the three main sins in education and how to avoid or overcome them. This community service activity uses the Participatory Action Research (PAR) method to collect data and provide assistance. During this activity, the students attentively followed the material presentation and looked enthusiastic, especially during the educational video about bullying and the question and answer segment. Through a question and answer session that discusses strategies for combating the 3 major sins in education, the author can assess the extent of students' understanding.